2019
DOI: 10.3389/fgene.2019.00163
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing Protein Traffic to the Primary Cilium

Abstract: The primary cilium is able to maintain a specific protein composition, which is critical for its function as a signaling organelle. Here we introduce a system to synchronize biosynthetic trafficking of ciliary proteins that is based on conditional aggregation domains (CADs). This approach enables to create a wave of ciliary proteins that are transported together, which opens novel avenues for visualizing and studying ciliary import mechanisms. By using somatostatin receptor 3 (SSTR3) as model protein we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…In the newt retina, SST 3 has been detected in the inner segment of cones and in the connecting cilia of rods, which correspond to the outer photoreceptor segments [78]. This is in agreement with the demonstration that SST 3 is localized in the neuronal cilia in many brain regions, in which it might play a role as chemical sensor [79] or in ciliary trafficking [80]. SST 4 is localized in the ganglion cells in both mouse [60,67] and rat [81] retinas.…”
Section: The Somatostatinergic System In the Retina And In The Hipsupporting
confidence: 76%
“…In the newt retina, SST 3 has been detected in the inner segment of cones and in the connecting cilia of rods, which correspond to the outer photoreceptor segments [78]. This is in agreement with the demonstration that SST 3 is localized in the neuronal cilia in many brain regions, in which it might play a role as chemical sensor [79] or in ciliary trafficking [80]. SST 4 is localized in the ganglion cells in both mouse [60,67] and rat [81] retinas.…”
Section: The Somatostatinergic System In the Retina And In The Hipsupporting
confidence: 76%
“…We chose MDCK cells that form an epithelial monolayer with apico-basal polarity for this assay because these cells had previously been used for this approach. 56,57 Studying nephrin trafficking this way, we observed no nephrin on the cell surface before the induction of ER release ( Figure 4H, upper panels), indicating successful ER retention. Upon exposure to D/D solubilizer, we observed trafficking of nephrin toward the apical cell surface over time ( Figure 4H, lower panels).…”
Section: Tbc1d8b Interacts With the Slit Diaphragm Protein Nephrin Anmentioning
confidence: 95%
“…Quantification of cell surface arrival of nephrin was done as described previously, with a custom-written MATLAB program. 56,57 Immunoblotting, Immunoprecipitation, Pull-Down Assay, and Immunofluorescence Staining Immunoblotting, immunoprecipitation, and immunofluorescence staining were performed as described previously. 58 Briefly, HEK293T were lysed and precleared using rec-Protein A-Sepharose 4B Conjugate (Life Technologies) overnight.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that EGFP:HDAC6 transfected cells displayed weak immunolabeling for aaTub compared to control EGFP-transfected cells or neighboring untransfected cells ( Figure 7 A–L), a result that validates the expected targeting of aaTub by HDAC6. In control EGFP-transfected cells, cilia were detectable but weakly labeled with aaTub, a possible transfection-related issue that has been shown to affect primary cilia aaTub staining in other studies [ 35 ]. Nevertheless, we did not observe cilia loss on these EGFP:HDAC6-expressing cells.…”
Section: Resultsmentioning
confidence: 99%